INFANCY WITHIN ADVERTISING PLATFORM: YOUNG CHILDREN EXPERIENCES ON A VIDEO-SHARING WEBSITE. - Aggio, Amanda (AoIR Selected Papers of Internet Research, 2019)
This paper investigates how young children experience digital advertising platforms. Specifically, it focuses on young children's participation in the YouTube app as part of an advertising mechanism that captures and profits from their views and attention. An innovative trans-disciplinary bridge between digital labour studies, biopolitics theory and qualitative research on children online has been developed to achieve this aim. The fact that children are going online progressively earlier raises critical questions around what they are experiencing in the virtual world. Data has become a way to profit and digital technology has become the infrastructure for capitalism permanence. This process of making a profit on user’s information leads to issues around trust and the confluence of surveillance and profit. It also raises questions around the persistence of Marxist concepts such as surplus labour, surplus value, and labour exploitation within the platform economy. Furthermore, in this environment one cannot disregard the relationship of power and the government of life; biopolitics should not be dissociable from capitalism. Thus, considering the early stage of young children’s cognitive development and their consequent vulnerability is urgent to understand how young children contribute to the political economy of the digital platform. The extent to which parents/caregivers and teachers are knowledgeable about the models of data mining, statistical profiling and corporate profit-generation that occur within this digital environment is also being investigated.